133k views
4 votes
Simplify: 36÷{12-(3+6)*5}​

User Hypino
by
4.9k points

2 Answers

4 votes

Answer:

12/11

Explanation:

Any work inside parentheses must be done first.

Thus, start with (3 + 6); this equals 9. Then the original expression becomes

36÷{12-(9)*5}

Multiplication and division are done before addition and subtraction. Thus, the next stp is to multiply 9 and 5, obtaining 45, inside the parentheses. This results in

36÷{12-45}, or 36÷{33}, which leads to the answer 36/33, or 12/11.

User Moiz Tankiwala
by
5.0k points
1 vote
Answer - 3

B = 36/ (12-9*5)
B = 36/ (12- 45)
B = 36/ (-33)
E = N/A
D = 3
M = N/A
A = N/A
S = N/A
User Abhishek Aravindan
by
4.7k points